Manajemen Pengelolaan Modal Pedagang Pasar Tradisional (Studi Kasus di Pasar Impres Kota Lhokseumawe) (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
The purpose of this study was to find out and describe "Capital Management of Traditional Market Traders at the Pasar Impres in Lhokseumawe town". The capital was obtained from money gathering activities (arisan). The problem is how to manage the capital of traditional market "pasar impres" traders in the Lhokseumawe town? This study used a descriptive qualitative method where data collection techniques were carried out through interviews and observation. The results of this study indicate that the low educational factor causes many traditional market traders to lack understanding of capital management issues and many traders to be less concerned about adding business capital from the "arisan" they have participated in. Some traders use the money for personal gain, and some other traditional market traders use it for additional business capital. So, the field of capital management turns out that it is not enough to show good management, this can be seen from the "arisan" money earned is not used to develop other businesses.